Dictionary of Physics - Ltd, Palgrave Macmillan (Palgrave Macmillan UK, 2004)
The "Dictionary of Physics" is a major reference source in the vast and dynamic field of physics that caters for both the undergraduate and graduate student. Spanning the space between the primary literature and educational texts, it encompasses 16,000 entries and 1.8 million words in four volumes